Functional lateralization of the medial prefrontal cortex in the modulation of anxiety in mice: Left or right? - Costa, N. S. [UNESP]; Vicente, M. A. [UNESP]; Cipriano, A. C. [UNESP]; Miguel, T. T. [UNESP]; Nunes-De-Souza, R. L. [UNESP] (Elsevier, 2016)
It has been suggested that the left medial prefrontal cortex (LmPFC) has an inhibitory role in controlling the right mPFC (RmPFC), thereby reducing the deleterious effects of stressors on emotional states. Here, we investigated the effects on anxiety of bilateral or unilateral injections of NOC-9 [a nitric oxide (NO) donor] and cobalt chloride (CoCl2; a synaptic inhibitor) into the mPFC of mice exposed to the elevated plus-maze (Experiments 1 and 2). The effects of restraint or social defeat on anxiety in undrugged mice were recorded at 5 min or 24 h after exposure to the stress (Experiment 3). Experiment 4 investigated the effects of LmPFC injection of CoCl2 combined with restraint or social defeat on anxiety, which was recorded 24 h later. Although intra-RmPFC NOC-9 produced anxiogenesis, its injection into the LmPFC, or bilaterally, did not change anxiety. Intra-RmPFC or -LmPFC injection of CoCl2 produced anxiolytic- and anxiogenic-like effects, respectively. Both restraint and social defeat produced anxiogenesis at 5 min, but defeated mice did not display anxiety 24 h after the stress. Although intra-LmPFC CoCl2 did not change anxiety, which was recorded 24 h later in non-stressed mice, this synaptic inhibitor produced a clear, anxiogenic-like effect in defeated (but not restrained) mice. These results suggest that (i) nitrergic activation of the RmPFC increases anxiety, which in turn is inhibited by NO production within the LmPFC; (ii) neuronal inhibition of the RmPFC or LmPFC elicits anxiolysis and anxiogenesis, respectively; and (iii) inactivation of the LmPFC results in recrudescence of anxiety induced by social defeat stress.
Keywords: Anxiety; Functional lateralization; Mice; mPFC; Stress